„Wspomnienia wygnanki” Pauliny Krakowowej – robinsonada z perspektywy kobiecej. Re-lektura - Berkan-Jabłońska, Maria (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
The aim of the article is to remind Paulina Krakowowa’s robinsonade “Memories of the exile” created in 1843, and to indicate the possible directions of its contemporary reading. The analysis covers the female characters appearing in the novel, their strategies accepted in the face of unfavorable circumstances, as well as the pro-civilizational actions undertaken already on the abandoned island. According to the author of the article these depictions could have a double meaning for the Polish writer: both feminist and patriotic. A separate issue indicated in the sketch is the positioning of Krakowowa’s work in the context of the Western European female robinsonades of the eighteenth and nineteenth century which have been already the subject of attention of such researchers as e.g. Jeannine Blackwell, Thomas Fair, and Michelle Smith.
“Memoirs of the Exile” by Paulina Krakowowa – Robinsonade from the Female Perspective. Re-reading
Keywords: Paulina Krakowowa; Robinson Crusoe; female robinsonades; female Crusoe; 19th-century emancipation; kobiece robinsonady; kobieta Crusoe; emancypacja XIX wieku